An interdisciplinary activity to teach the concept of pH in chemistry. (26th January 2022) - Pereira, Waylla de Souza; Fernandes, Julio C. B.
Abstract: This work describes an alternative approach for introducing the concept of pH in high school. We develop an experimental protocol to demonstrate in classroom as pH affects the life of microorganisms. At the same time, we constructed low-cost equipment and a homemade culture media using ordinary products, which they are easily found by the teachers in any commercial store. It was observed that in pH lower than 3 and higher than 13 the growth of microorganisms is inhibited. We applied this interdisciplinary activity to students from six different schools. The results showed that teaching the concept of pH, contextualized with its effect on the growth of microorganism, was significant for the students. Our goal with this kind of activity is to allow students to understand the concept of pH through the application of knowledge allowing them to intervene in their daily lives. Supplementary materials for this article are available at https://doi.org/10.1080/00368121.2021.1977225